PERANCANGAN DAN PENGUJIAN SISTEM MONITORING OPERASI ALAT PENGERING LADA MENGGUNAKAN TEKNOLOGI ARDUINO - Reynaldi Pratama; Nabawi Imron; Indra Feriadi; Zanu Saputra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Pepper dryer technology often results in an unstable process that affects the drying consistency. This study aims to obtain a monitoring system for temperature, hot air velocity, and humidity of a pepper dryer using Arduino technology. The design of electrical hardware tools using "Fritzing" software. The system components use Arduino as a microcontroller and DS18B20 temperature sensor, DHT22 humidity sensor, wind speed sensor and LCD. System testing was carried out on a pepper dryer to determine the system's ability to measure and display the results of temperature, air velocity and humidity sensor measurements. The measurement of sensor accuracy is carried out by comparing the results of system measurements on the LCD with a thermometer, anemometer and hygrometer in the span of 15, 30, 45, and 60 minutes. The test results show that the drying system operating parameter monitoring system is able to measure and display the results on the LCD with a temperature parameter error rate of 0.54% (99.46%), air flow velocity 0.3% (99.7% accuracy) and humidity. 0% (100% accuracy). The test results show that the drying system's operating parameter monitoring system is able to measure and display the results on the LCD with an accuracy of 0.54% temperature, +/- 1.25% air velocity and 0% humidity. The value of the monitoring results is used as an indicator to regulate the temperature and air velocity can be maintained according to the required value, while the humidity value indicates the water content in the material.